ANALISIS BIBLIOMETRIK PENELITIAN INTRUSI AIR LAUT DI ESTUARI - Zainuri, Ahmad; Lihawa, Fitryane; Hasim; Wahyuni K Baderan, Dewi; Mahmud, Marike; Yusuf, Daud (Jurnal Biogenerasi, 2024)
This study uses a quantitative approach with bibliometric methods to evaluate research publications on seawater intrusion in estuaries. The data used are scientific articles indexed by Scopus from 2020 to 2024 with 4 keywords namely Seawater intrusion AND Coastar OR Estuary. The research steps include identification of research objectives, data collection, data preprocessing, bibliometric analysis, interpretation of results, and conclusions. The results showed that research on seawater intrusion in estuaries increased from 2020 to 2024. The highest increase occurred in 2023 with 1110 articles. As of March 2024, there have been 433 articles related to seawater intrusion in estuaries. The most studied field of seawater intrusion in estuaries is Environmental Science with 2628 articles, followed by earth and planetary sciences with 2293 articles, agricultural and biological sciences with 2074 articles, and the least is about Veterinary Science and Veterinary Medicine with 29 articles. The development map of research linkages on seawater intrusion in estuaries can be grouped into six clusters. Cluster 1 consists of 11 themes, namely ecological risk, eutrophication, hypoxia, phytoplankton, remote sensing, salinity, suspended particulate matter, tropical estuary, water quality, zooplankton. Cluster 2 consists of 9 study themes, namely estuary, fish, heavy metals, mangrove, microplastics, organic matter, pollution, risk assessment, sediment. Cluster 3 consists of 8 study themes, namely coastal aquifer, dentrification, groundwater salinization, hydrogeochemistry, microbial community, nitrate, seawater intrusion, stable isotopes. Cluster 4 consists of 6 study themes, namely antibiotic resistance genes, climate change machine learning, sea level rise, spatial distribution, tide. Cluster 5 consists of three themes, namely numerical modelling, submarine groundwater dischange, tides. Cluster 6 consists of one theme, namely numerical modelling.